2001
DOI: 10.1111/j.1442-2050.2001.00156.x
|View full text |Cite
|
Sign up to set email alerts
|

Perforation of a gastric tube peptic ulcer into the thoracic aorta

Abstract: We present a case of a 52-year-old male patient who died from massive hematemesis as a result of perforation of a benign peptic ulcer into the descending thoracic aorta, 1 year after esophagectomy for esophageal cancer and gastric tube interposition. We also review the literature for mechanisms of ulceration in intrathoracic gastric grafts and for complications of such ulcers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Reports on gastric tube ulcer formation after gastric substitution for oesophageal cancer suggest an incidence of 1-6.6% [7,8]. When these ulcers eventually become symptomatic, serious and often fatal complications can occur due to haemorrhage, perforation into adjacent intrathoracic structures and fistula formation [1].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reports on gastric tube ulcer formation after gastric substitution for oesophageal cancer suggest an incidence of 1-6.6% [7,8]. When these ulcers eventually become symptomatic, serious and often fatal complications can occur due to haemorrhage, perforation into adjacent intrathoracic structures and fistula formation [1].…”
Section: Discussionmentioning
confidence: 99%
“…We reviewed the patients' childhood operation reports, which showed that the gastric antrum had been brought up to the cervical oesophagus (reverse gastric tube). Reverse gastric tubes are potentially more susceptible to ulcer formation than isoperistaltic ones, because the interposition of a reverse gastric tube does not require a bilateral truncal vagotomy [1]. Furthermore, food passage and release of antral gastrin, are known to intensify acid production in the fundus, thus predisposing to ulcer formation [6,9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9][10][11][12][13][14][15][16][17] The characteristics of the cases of perforated gastric tube after esophagectomy for esophageal cancer are presented in Table 1. Cases #6 12 and #11 15 had been taking an H2-blocker and nonsteroidal anti-infl ammatory drugs (NSAIDs), respectively, before the gastric tube was perforated, and the latter patient had a history of gastric ulcers.…”
Section: Case Reports On Perforated Gastric Tubesmentioning
confidence: 99%
“…Although such lesions are considered to be rare postoperative complications, 5 they are often asymptomatic, and so in many cases there have been sudden instances of hematemesis, anemia, severe pain, or shock, among other symptoms. 6 We therefore searched the literature for cases of perforated gastric tubes in patients treated for esophageal cancer, and examined their characteristics and the mechanisms of ulceration.…”
Section: Introductionmentioning
confidence: 99%